Georgia : Fifth Review Under the Stand-By Arrangement and Request for Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses key findings of the Fifth Review Under the Stand-By Arrangement for Georgia. The 2010 program sets out a viable exit strategy from official external support, permitting the Georgian authorities to return to capital markets ahead of their large debt rollover needs in 2013-14. Fiscal consolidation remains based on expenditure containment both in 2010 and over the medium term. The authorities are enhancing banking sector supervisory capacity and raising its efficiency. Reflecting improved liquidity conditions, deposit interest rates have decreased but remain high.